2018
DOI: 10.5755/j01.ppaa.17.3.21952
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Incentives of Civil Servants in Lithuanian Municipalities

Abstract: Effective public management cannot be imagined without an efficiently functioning civil service apparatus. It is often stated that people working in the civil service are driven by idealistic motives, however, to ensure the implementation of the state's objectives, the efficiency and quality of civil servant activities, adequate motivational incentives of civil servants are necessary. The article analyzes theoretical and analytical aspects of the motivational incentives of civil servants: the concept of incent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…The findings align with Sun (2019) who suggests that methods used in the in-service training for the civil servants should be more student-focused, the cognition function development-aimed, and function-through-context-based. The study supports the implications made by Druskiene & Sharkunaite (2018) what claimed that it is not just idealistic motives that motivate the civil service but the balanced motivation system including monetary, moral, political, normative, and emotional stimuli. Further research is needed to identify the COM-B model that can be used at colleges and universities to train student civil service managers.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The findings align with Sun (2019) who suggests that methods used in the in-service training for the civil servants should be more student-focused, the cognition function development-aimed, and function-through-context-based. The study supports the implications made by Druskiene & Sharkunaite (2018) what claimed that it is not just idealistic motives that motivate the civil service but the balanced motivation system including monetary, moral, political, normative, and emotional stimuli. Further research is needed to identify the COM-B model that can be used at colleges and universities to train student civil service managers.…”
Section: Discussionsupporting
confidence: 82%
“…The review of the relevant literature found that in contrast to the private sector, employees of the public sector are under-motivated financially and it is very important that the feeling of accomplishment could be influenced more intensively (Andersen et al, 2020). Though the public service motivation is seen by the community as the self-stimulated desire of the civil servant to create an environment of wellbeing, the public-interest-commitment is gradually decreasing in both the civil service applicants and employees (Druskiene & Sharkunaite, 2018;Leisink et al, 2018). Perry (2015) along with Thompson & Christensen (2018) suggest stimulating the feeling of importance in the civil servants in terms of their contribution to organisational goals increases their job commitment which results in increased governance effectiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Es necesario que las instituciones se centren en la voluntad de los funcionarios para contribuir a la creación del bienestar social, proporcionando servicios públicos de calidad que satisfagan los intereses públicos, basados en los principios de democracia, cooperación, responsabilidad, rendición de cuentas, estrategia, pensamiento, productividad y rentabilidad (Druskienė & Šarkiūnaitė, 2018).…”
Section: Administración Pública Y Funcionario Públicounclassified